Reliability and Risk Analysis of Lubrication System on Sabuk Nusantara 43 - Suardi, Suardi; Setiawan, Wira; Alamsyah, Alamsyah; Wulandari, Amalia Ika; Hidayat, Taufik (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2023)
This study aims to present a systematic approach to evaluating the reliability of the lubrication system on the Sabuk Nusantara 43. The methods used in conducting risk assessments are quantitative methods and qualitative methods or semi-quantitative methods. In the quantitative method, the approach taken is more to the value (number) approach. Meanwhile, in the semi-quantitative method, the approach used is a qualitative approach and a quantitative approach. This method can identify potential events that not only cause disruption to pipeline operations but also events related to safety and the environment. The results showed that the biggest risk in the installation of Sabuk Nusantara 43 lubricant was found in the filter section with damage levels reaching five times in one year with risk matrix plotting in the major category (Not Acceptable) and risk control options (recommendation). Selection of filter components that are better and fulfill standards of existing rules, regular maintenance and checking, and avoiding the use of lubricating oil that is too old and used.